Implementation of “Merdeka Belajar”: Evolving Learner Autonomy and Speaking Skill through Cultural Discovery Learning Model - Rafiqa, Rafiqa; Aswad, Muhammad; Asfihana, Raida; Singh, Amreet Kaur Jageer (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: The current implemented curriculum is Merdeka Belajar Kampus Merdeka (MBKM). It highlights the independence and freedom of the students in learning. MBKM is expected to overcome the learning loss after the pandemic covid 19. This study intends to investigate the students’ learner autonomy and speaking skill after implementing the cultural discovery learning model. Methodology: The study attempted Classroom Action Research (CAR). This research was conducted at Universitas Sulawesi Barat for one semester in the Speaking for Professional. The number of research subjects was 20 students of the English Education Department for the 2021 academic year. Findings: Based on the learning independence table in cycle 2, it shows that the average student confidence in learning, whether it is expressing opinions, expressing ideas, asking questions or giving answers, is good. The data shows that students are quite disciplined in learning, and also good at taking the initiative in the learning process. Conclusion: It can be concluded that the implementation of Merdeka Belajar through cultural discovery learning can increase learning independence in the Speaking for Professional course for 4th-semester students of the University of West Sulawesi. Moreover, the implementation of Merdeka Belajar through cultural discovery learning can improve the English speaking skills of 4th-semester students of the University of West Sulawesi. Originality: This study focused on the Cultural Discovery Learning Model as one way to implement the MBKM curriculum. The further researcher is expected to identify the students' perception of it and attempt another method to implement the current curriculum.